Primitive genotypic characteristics in umbilical cord neutrophils identified by single-cell transcriptome profiling and functional prediction - Chen, Yi; Huang, Jiamin; Guo, Zaiwen; Zhu, Zhechen; Shao, Yiming; Li, Linbin; Yang, Yunxi; Yu, Yanzhen; Liu, Lu; Sun, Bingwei (Frontiers in Immunology, 2022)
The function and heterogeneity of neutrophils in neonatal umbilical cord blood (UCB) have not been characterized.  In this study, we analyzed the neutrophils in UCB and healthy adults using single-cell RNA sequencing analysis for the first time. We found that neutrophils divided into six subpopulations (G2, G3, G4, G5a, G5b, and G5c) with different marker genes and different functions under homeostasis.  Compared with healthy adults, neutrophils of UCB were more naïve and have more obvious degranulation and activation functions. Moreover, we found significant differences in the amount and function of G5b cells between healthy adults and UCB. The amount of G5b group in UCB was lower, but it has more degranulation, secretion and activation functions.  In addition, we noted a new subset of G5c labeled by CD52, which almost did not exist in UCB. Besides, its differential genes were enriched in terms such as protein synthesis and mRNA transcription.  Furthermore, uncharacteristic transcription factors ZNF-276, ZNF-319 and ZNF-354A were identified in our study. In summary, we first examined the heterogeneity and functional diversity of neutrophils in UCB, and these data provided new insights into the mechanism of neutrophil-related diseases of neonates and the wider use of neutrophils in UCB.